Student Abilities During the Expansion of US Education - Lutz Hendricks; Todd Schoellman (Center for Economic Studies and ifo Institute (CESifo), 2013)
The US experienced two dramatic changes in the structure of education in a fifty year period. The first was a large expansion of educational attainment; the second, an increase in test score gaps between college bound and non-college bound students. We study the impact of these two trends on the composition of school groups by observed ability and the importance of these composition effects for wages. Our main finding is that there is a growing gap between the abilities of high school and college-educated workers that accounts for one-half of the college wage premium for recent cohorts and for the entire rise of the college wage premium for the 1910-1960 birth cohorts.
Keywords: I20; J24; 330; education; ability; skill premium